Economic efficiency of short-term versus long-term water rights buyouts - Wheeler, Erin; Golden, Bill; Johnson, Jeffrey; Peterson, Jeffrey M. (My University, 2012)
Because of the decline of the Ogallala Aquifer, water districts, regional water managers, and state water officers are becoming increasingly interested in conservation policies. This study evaluates both short-term and long-term water rights buyout policies. This research develops dynamic production functions for the major crops in the Texas Panhandle. The production functions are incorporated into optimal temporal allocation models that project annual producer behavior, crop choices, water use, and aquifer declines over 60 years. Results suggest that long-term buyouts may be more economically efficient than short-term buyouts.
Keywords: Dynamic production function; nonlinear optimization; Ogallala aquifer; Water rights buyout